2014
DOI: 10.1007/s00424-014-1473-7
|View full text |Cite
|
Sign up to set email alerts
|

Low K+ current in arterial myocytes with impaired K+-vasodilation and its recovery by exercise in hypertensive rats

Abstract: K(+) channels determine the plasma membrane potential of vascular myocytes, influencing arterial tone. In many types of arteries, a moderate increase in [K(+)]e induces vasorelaxation by augmenting the inwardly rectifying K(+) channel current (I Kir). K(+)-vasodilation matches regional tissue activity and O2 supply. In chronic hypertension (HT), small arteries and arterioles undergo various changes; however, ion channel remodeling is poorly understood. Here, we investigated whether K(+) channels and K(+)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In rats, angiotensin II-induced hypertension reduces SMC K IR channel current density and K + -induced dilation of skeletal muscle and cerebral arteries (1281). In the skeletal muscle artery SMCs, 2 weeks of exercise training reversed the effects of hypertension on K IR channel currents and K + -induced dilation (1281).…”
Section: Kir Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, angiotensin II-induced hypertension reduces SMC K IR channel current density and K + -induced dilation of skeletal muscle and cerebral arteries (1281). In the skeletal muscle artery SMCs, 2 weeks of exercise training reversed the effects of hypertension on K IR channel currents and K + -induced dilation (1281).…”
Section: Kir Channelsmentioning
confidence: 99%
“…In the skeletal muscle artery SMCs, 2 weeks of exercise training reversed the effects of hypertension on K IR channel currents and K + -induced dilation (1281). While K IR channel currents were restored by exercise in cerebrovascular myocytes, K + -induced dilation remained depressed (1281) suggesting regional heterogeneity in the response to exercise training. Previous studies showed that exercise training augments expression and function of vascular SMC K IR channels (709).…”
Section: Kir Channelsmentioning
confidence: 99%
“…The changes in Kir channels during hypertension are currently inconclusive. Previous studies have shown a reduced function of Kir channels during hypertension [61], which complements the compensatory upregulation of the neuronal nitric oxide synthase (nNOS) pathway [11] and an increase in nonselective cationic current [61] to reduce organ blood flow. However, other studies have demonstrated that upregulation of Kir channels in cerebral microvessels acts as an adaptive mechanism to preserve cerebral blood flow during chronic hypertension [53].…”
Section: Changes In Kir Channels During Hypertensionmentioning
confidence: 98%
“…The effects of hypertension on K IR channel function are not clear; increases (Nakahata et al, 2006), decreases (Seo et al, 2014), or no change in function (Tajada et al, 2012) have been reported. Similarly, diabetes has been reported to increase (Troncoso Brindeiro et al, 2008; Troncoso Brindeiro, Lane, & Carmines, 2012) or decrease (Matsushita & Puro, 2006; Mayhan, Mayhan, Sun, & Patel, 2004; Vetri et al, 2012) K IR channel function in different models.…”
Section: Potassium Channels and Regulation Of Vsm Contractionmentioning
confidence: 99%